Colorectal cancer burden and trends: Comparison between China and major burden countries in the world - Zhou, Jiachen (Chin J Cancer Res, 2021)
OBJECTIVE: To summarize the colorectal cancer (CRC) burden and trend in the world, and compare the difference of CRC burden between other countries and China. METHODS: Incidence and mortality data were extracted from the GLOBOCAN2018 and Cancer Incidence in Five Continents. Age-specific incidence trend was conducted by Joinpoint analysis and average annual percent changes were calculated. RESULTS: About 1.85 million new cases and 0.88 million deaths were expected in 2018 worldwide, including 0.52 million (28.20%) new cases and 0.25 million (28.11%) deaths in China. Hungary had the highest age-standardized incidence and mortality rates in the world, while for China, the incidence and mortality rates were only half of that. CRC incidence and mortality were highly correlated with human development index (HDI). Unlike the rapid increase in Republic of Korea and the downward trend in Canada and Australia, the age-standardized incidence rates by world standard population in China and Norway were rising gradually. The age-specific incidence rate in the age group of 50−59 years in China was increasing rapidly, while in Republic of Korea and Canada, the fastest growing age group was 30−39 years. CONCLUSIONS: The variations of CRC burden reflect the difference of risk factors, as well as levels of HDI and screening (early detection activities). The burden of CRC in China is high, and the incidence of CRC continues to increase, which may lead to a sustained increase in the burden of CRC in China in the future. Screening should be expanded to control CRC, and focused on young people in China.